Two Acylated Isoscutellarein Glucosides with Anti-Inflammatory and Antioxidant Activities Isolated from Endemic Stachys Subnuda Montbret & Aucher ex Benth - DOĞAN, AHMET; ŞEN, ALİ; BİTİŞ, LEYLA (SLOVENSKO KEMIJSKO DRUSTVO, 2019)
In this study, we report anti-inflammatory and antioxidant activities of two acylated isoscutellarein glucosides isolated from ethyl acetate extract of Stachys subnuda aerial part. 4'-O-methylisoscutellarein-7-O-2 ''-O-(6 ''' acetyl-beta-D-allopyranosyl)-beta-D-glucopyranoside (SS1) and isoscutellarein-7-O-2 ''-O-(6 '''-O-acetyl-beta-D allopyranosyl)-beta-D -glucopyranoside (SS2) were isolated as major compounds from ethyl acetate extract (SSEA). Also, 2 hydroxycinnamic acid derivatives, and 5 isoscutellarein glucoside derivatives in the SSEA were identified using LC-MS/MS. SS1 with IC50 values of 2.35 and 1.98 mu g/mL and SS2 with IC50 values 13.94 and 12.76 mu g/mL showed fairly strong antioxidant activity against DPPH (1,1-diphenyl-2-picrylhydrazyl) and ABTS (2,2'-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid) radicals, respectively. SS1 and SS2 inhibited 5-lipoxygenase (5-LOX) activity with IC(50 )values of 47.23 and 41.60 mu g/mL, respectively. The results demonstrated that SS1 and SS2 have significant anti-inflammatory and antioxidant potential. Acylated flavonoid glycosides have been first reported for Stachys subnuda. Also, the activities of SS1 and SS2 have been investigated for the first time in this study.
Keywords: Stachys subnuda; acylated flavonoids; anti-inflammatory activity; antioxidant activity; LC-MS/MS; MOUNTAIN TEA; FLAVONOID GLYCOSIDES; BIOLOGICAL-ACTIVITY; L.; METABOLITES; LAMIACEAE; PROFILE